Python tools for Visual Studio : leverage the power of the Visual Studio IDE to develop better and more efficient Python projects - Sabia, Martino (Community experience distilled., 2014)
This is a hands-on guide that provides exemplary coverage of all the features and concepts related to PTVS. The book is intended for developers who are aiming to enhance their productivity in Python projects with automation tools that Visual Studio provides for the .Net community. Some basic knowledge of Python programming is essential.